PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 103 PALEMBANG - Hutagalung, Try Yulianty Marito; M. Taheri Akbar; Arief Kuswidyanarko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of Indonesian Realistic Mathematics Education (PMRI) approach on mathematics learning outcomes of fifth grade students of SDN 103 Palembang. The research method used is quantitative experimental method. The data collection technique of this research is a test. This research design is a quasi experiment type nonequivalent control group design. The results of data processing from the research that has been done obtained the average value of the control class pretest 51.63, experimental class pretest 51.73, control class posttest 61.78 and experimental class posttest 85.70. The normality test results show that the samples come from a normally distributed population. The homogeneity test results show the variance in each group is the same (homogeneous). The results of the independent sample t-test hypothesis test showed a 2-tailed significance value of 0.000 so that Sig. 0.000 <0.05 with a tcount value of 11.176 and ttable 2.00404 so that tcount> ttable. Thus Ho is rejected and Ha is accepted which means that there is an effect of the influence of the Indonesian Realistic Mathematics Education (PMRI) approach on the mathematics learning outcomes of fifth grade students of SDN 103 Palembang.